Role of household waste, governance quality, and greener energy for public health: Evidence from developed economies - Wei, Jiping; Xu, Lihua; Zhou, Jing (Frontiers in Public Health, 2022)
In the current times, the global economies and international organizations declared that pollution is one of the prominent causes of declined human health. Still, most literature is biased toward economic sustainability and ignores such vital issues. The current study tends to identify the factors affecting public health in the Group of Seven economies except for Italy (G6). Specifically, this study aims to investigate the influence of household waste (HHW), bureaucratic quality (BQ), democratic accountability (DA), urbanization growth (URP), GDP per capita, and renewable energy use (EPR) on public health, throughout 1996-2020. This study uses advanced panel data approaches and finds the heterogeneity of slope coefficients, the dependence of cross-sections, and the persistence of cointegration between the variables. The asymmetric distribution of data leads to employing the novel method of moment quantile regression. The estimated results reveal that URP, GDPPC, and EPR significantly increase domestic general government health expenditures, improving public health. However, HHW and BQ adversely affect public health by reducing health expenditures. The robustness of the results is tested via utilizing the panel quantile regression. Based on the empirical findings, this study suggests policies regarding the improvement in public heakth expenditure, R&D investment, spending in renewable energy sector, and strengthening of the institutional quality.